The Study of Slag Cement’s Microstructural Properties - Saida Boualleg (Université de M'sila, 2021)
The objective of this work is the quantification of hydration in cement. To monitor this quantity of hydrated cement "hydration degrees" we adopted the method of thermogravimetric analysis (TGA) which allowed us to determine the degree of hydration α(t), bound water (WB) and non-evaporable water. This study is completed by the analysis of diffractometers (DRX). Cements containing different percentages of slag. The evolution of the kinetics was studied during 3, 7 and 28 days. According to the results obtained, the hydration rate is inversely proportional to the addition content in the cement. The degree of hydration is directly related to the formation of hydrates and portlandite, more non-evaporable water retained in the hydrates corresponds to a high degree of hydration. This technique is coupled with the carbonation and strength of ordinary mortar. The experimental data obtained have been correlated and interpreted with regard to the evolution of strength and carbonation as a function of the degree of hydration, bound water and non-evaporable water of the cement hydrates. The Bhatty method is verified for the calculation of the degree of hydration and can be successfully applied for composite cements.
Keywords: hydration, bound water, degrees of hydration, slag, strength, thermogravimetric analysis, portlandite, non-evaporable water